2019
DOI: 10.1021/acs.analchem.9b01659
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Nontargeted Platform Using Two-Dimensional Gas Chromatography Time-of-Flight Mass Spectrometry Integrating Computer-Assisted Structure Identification and Automated Semiquantification for the Comprehensive Chemical Characterization of a Complex Matrix

Abstract: Nontargeted screening methodologies are powerful approaches for comprehensive chemical characterization of complex matrixes. In order to maximize chemical space coverage, three analytical methods using two-dimensional gas chromatography with time-of-flight mass spectrometry for nonpolar, polar, and volatile compounds have been established. The structural identification process was streamlined with an in-house developed computer-assisted structure identification platform, which facilitated the identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…During this method evaluation process, it was observed that the number of compounds identified to be present in the smoke of the 3R4F reference cigarette increased exponentially as their concentration decreased. By extrapolating this exponential trend and comparing the anticipated number versus the actual number of compounds identified, a point was reached at a concentration of 100 ng/item, below which the actual number of compounds identified was consistently lower than expected, which was interpreted as being the lower limit of the working range for the methodology [18]. While the number of compounds increased as their concentrations decreased, the mass contribution relative to the total chemical space identified declined logarithmically and the accumulated total mass for compounds below 100 ng/item for 3R4F was estimated to be less than 1% of the total mass amenable by GC×GC-TOFMS analysis [18].…”
Section: Aerosol Generation and Analysismentioning
confidence: 98%
See 4 more Smart Citations
“…During this method evaluation process, it was observed that the number of compounds identified to be present in the smoke of the 3R4F reference cigarette increased exponentially as their concentration decreased. By extrapolating this exponential trend and comparing the anticipated number versus the actual number of compounds identified, a point was reached at a concentration of 100 ng/item, below which the actual number of compounds identified was consistently lower than expected, which was interpreted as being the lower limit of the working range for the methodology [18]. While the number of compounds increased as their concentrations decreased, the mass contribution relative to the total chemical space identified declined logarithmically and the accumulated total mass for compounds below 100 ng/item for 3R4F was estimated to be less than 1% of the total mass amenable by GC×GC-TOFMS analysis [18].…”
Section: Aerosol Generation and Analysismentioning
confidence: 98%
“…By extrapolating this exponential trend and comparing the anticipated number versus the actual number of compounds identified, a point was reached at a concentration of 100 ng/item, below which the actual number of compounds identified was consistently lower than expected, which was interpreted as being the lower limit of the working range for the methodology [18]. While the number of compounds increased as their concentrations decreased, the mass contribution relative to the total chemical space identified declined logarithmically and the accumulated total mass for compounds below 100 ng/item for 3R4F was estimated to be less than 1% of the total mass amenable by GC×GC-TOFMS analysis [18]. A formal performance assessment specific for the LC-HRAM-MS methods has not yet been performed; however, the characteristics were assumed to be broadly comparable, and a 100 ng/item threshold was applied to data generated by both GC×GC-TOFMS and LC-HRAM-MS platforms, which served to optimize the proportion of substances identified relative to a practicable amount of effort applied for their identification.…”
Section: Aerosol Generation and Analysismentioning
confidence: 98%
See 3 more Smart Citations